Contribution of the Nahdlatul Ulama (NU) social movement to gender Issue and empowerment of women in Indonesia (1938-2022) - Irhamsyah, Fahmi; Anshor, Maria Ulfah (The International Journal of Pegon : Islam Nusantara civilization, 2023)
The study of gender and the social movements that are currently taking place has made the investigation of social movements into one of its most important areas of focus. Since its inception in 1938, the Nahdlatul Ulama social movement has been an essential component in the institutionalisation of gender equality and the advancement of women's rights. The findings of the study demonstrated that over the period between 1938 and 2022, the Nahdlatul Ulama social movement made a significant contribution to the evolution of Indonesian society, particularly as it pertained to concerns of gender equality. The social movement's contribution can be observed in the formation of public opinion as well as in the organisations or foundations that have a role to the creation of narratives and social institutions. Penelitian tentang gerakan sosial menjadi salah satu topik penting dalam mengkaji gender dan perubahan sosial yang terjadi. Gerakan sosial Nahdlatul Ulama sejak tahun 1938 telah menjadi bagian penting dalam upaya sosialisasi kesetaraan gender dan pemberdayaan perempuan. Hasil penelitian membuktikan bahwa sejak tahun 1938 hingga tahun 2022 kontribusi gerakan sosial Nahdlatul Ulama sangat besar dalam perubahan sosial khususnya terkait isu gender dan pemberdayaan perempuan di Indonesia. Bentuk kontribusi gerakan sosial Nahdlatul Ulama terlihat dari pembentukan opini publik hingga organisasi maupun Yayasan yang memiliki kontribusi dalam pembentukan narasi serta lembaga sosial.